Teori dan Model dalam Bimbingan dan Konseling : Existential Therapy pada Lansia dengan Sindrom Sarang Kosong - Renidayati, Renidayati; Karneli, Yeni (Jurnal Bidan Mandiri, 2025)
Empty Nest Syndrome is a psychosocial and existential condition commonly experienced by older adults when their children become independent and leave home. This transition often leads to loneliness, loss of life meaning, and changes in identity and family roles. This study aims to describe the application of Existential Therapy theories and techniques for older adults experiencing Empty Nest Syndrome in Padang City. A descriptive qualitative approach with a phenomenological design was employed to explore participants’ subjective experiences, emotional dynamics, and psychological needs. Data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis followed the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing, supported by source and technique triangulation. Findings reveal four major themes: emotional experiences of sadness and loss when children leave home; decreased meaning in life and identity crisis; strong influence of Minangkabau cultural values and social support; and the positive impact of Existential Therapy in reconstructing meaning, enhancing self-acceptance, and strengthening social relationships. Existential Therapy effectively assists older adults in adapting to family role changes and improving psychological well-being. This approach is recommended for integration into community-based counseling services for older adults.